Gore capitalism - Valencia Triana, Margarita 1980-; Valencia, Sayak; Pluecker, John, 1979- (South Pasadena : Semiotext(e), 2018)
"Written by the Tijuana activist intellectual Sayak Valencia, Gore Capitalism is a crucial essay that posits a decolonial, feminist philosophical approach to the outbreak of violence in Mexico and, more broadly, across the global regions of the Third World. Valencia argues that violence itself has become a product within hyperconsumerist neoliberal capitalism, and that tortured and mutilated bodies have become commodities to be traded and utilized for profit in an age of impunity and governmental austerity" -- Back cover.
Warning -- El incio = The beginning -- Introduction -- A clarification about gore : becoming-snuff -- The breakdown of the state as a political formation -- Capitalism as cultural construction -- The new mafia -- Necropolitics -- At the brin of El Bordo, I become blade : gore capitalism and feminism(s) -- Conclusions -- El merco inicio = The very beginning -- Notes -- Selected bibliography.
English translations of: Capitalismo gore. Barcelona : Melusina, 2010.
boek
Keywords: Capitalism -- Political aspects -- Developing countries; Capitalism -- Moral and ethical aspects -- Developing countries; Violence -- Political aspects -- Developing countries; Feminism -- Developing countries; Capitalism -- Moral and ethical aspects; Capitalism -- Political aspects; Feminism; Violence -- Political aspects; Developing countries; Essays; Essays